On-demand debonding multifunctional hydrogel as well as preparation method and application thereof

By introducing MOS2@TA/FE NTS and specific polymers in hydrogel, forming a multi -function hydraulic coating dressing with demand dehydration function solves the problem of single and difficult to adapt to wound changes. It realizes good adhesion, dehydration and antibacterial antioxidant performance, and promotes healing of wounds.

CN119371587APending Publication Date: 2025-01-28HUNAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411263904.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing hydrogel dressing has a single function and cannot meet the complex and diverse clinical needs in the healing process of infected wounds, and it is difficult to adapt to the changes in wound shape and secondary injuries caused by dressing replacement.

Method used

By using MOS2@TA/Fe NTS and polypropylene, 1-ethylene cpimraromazole, and acrylic-N-altericide polymerization, combined with the light thermal response of MOS2@TA/Fe NTS and 1-ethylene base The coordinating key of the imidazole groups to achieve the need for removing adhesion function of hydrogel.

Benefits of technology

The good adhesion and dehydration of hydrogel can be realized, can closely fit dynamic wounds, promote wound healing, reduce secondary damage during dressing, and have excellent antibacterial and antioxidant properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371587A_ABST
    Figure CN119371587A_ABST
Patent Text Reader

Abstract

The invention discloses an on-demand debonding multifunctional hydrogel and a preparation method and application thereof.Acrylic acid, 1-vinyl imidazole and acrylic acid N-succinimide ester are used as raw materials to form a copolymerization network, MoS2 (at) TA / Fe NTs are loaded, hydrogen bonds formed by acrylic acid and amino groups on the skin have the function of debonding on the skin, and the function of debonding on the skin is achieved. Imidazole of the 1-vinyl imidazole and a negatively charged group on the skin generate electrostatic interaction, an NHS group of the acrylic acid-N-succinimide ester and a primary amino group of skin tissue form a stable amido bond, and stable wet wound adhesion is achieved through the synergistic effect of the 1-vinyl imidazole, the acrylic acid-N-succinimide ester and the primary amino group of the skin tissue. Meanwhile, the function of on-demand debonding of the hydrogel can be realized by utilizing the good responsiveness of an imidazole group of 1-vinyl imidazole to zinc ions, the permeability and anabolism of bacterial cell membranes are influenced, the permeability of the cell membranes is changed, the hydrogel is endowed with excellent antibacterial activity in combination with the photo-thermal response of MoS2 (at) TA / Fe NTs, and the problems that an existing hydrogel dressing is single in function and poor in antibacterial activity are solved. The complex and diversified clinical requirements in the healing process of infected wounds cannot be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of hydrogel dressing preparation, and more specifically, relates to an on-demand debonding multifunctional hydrogel and a preparation method and application thereof. Background Art

[0002] The skin is the largest organ in the human body and has the largest exposed area. Once the skin is damaged, it may cause a series of health problems, such as inflammation, secondary injury and bacterial infection. In particular, the abuse of antibiotics will aggravate these problems, resulting in drug resistance in many bacteria. Bacterial infection is becoming one of the main factors hindering wound healing. Due to the limited self-repair ability of the human body, it brings serious physiological and psychological pressure to patients and increases the economic burden. The substrate and form of wound dressings are important factors that determine whether they can meet the needs of wound care. Traditional gauze and medical cotton are often in dry form. In wound care applications, they cannot provide a moist healing environment for the wound, which is not conducive to tissue regeneration and cell migration at the wound. Hydrogel is a 3D cross-linked hydrophilic polymer network with ultra-high water content. With its advantages of high water content, good flexibility and strong drug loading capacity, it has received widespread attention in the field of tissue engineering and medicine. Because hydrogels have porous structures and adjustable physical properties, biomolecules and metabolic wastes in the wound microenvironment can be effectively transported through them, providing good mechanical support for cell migration and proliferation, and isolating external pollution such as bacteria.

[0003] With the continuous diversification and refinement of clinical needs, the multifunctionality of hydrogel dressings is a research trend in the biomedical field. Molybdenum disulfide (MoS2) is a transition metal disulfide with good photothermal conversion efficiency in the visible and near-infrared regions, and has been shown to have superoxide dismutase and catalase activity. Tannic acid is a natural polyphenol compound that is widely found in plants. As a powerful antioxidant, tannic acid can neutralize and remove free radicals in the body, helping to prevent cell damage and aging caused by oxidative stress. In 2021106803579, a method for preparing tannic acid iron coordinated modified molybdenum disulfide hydrogel dressings is used to modify molybdenum disulfide by tannic acid coordination, and it is compounded with polyvinyl alcohol hydrogel to obtain tannic acid iron coordinated modified molybdenum disulfide hydrogel dressings, which have the properties of rapid self-healing and can be applied to different wounds. It has nanozyme activity, can produce hydroxyl radicals and photothermal conversion capabilities, and has efficient bactericidal and antioxidant properties against a variety of common bacteria. However, wound healing is a complex and continuous process, including hemostasis, inflammation, proliferation and remodeling, and different stages often have different functional requirements for dressings. In addition, the shape of the wound in the active and moving parts of the human body changes, which can easily cause the dressing to fall off, and it is easy to cause secondary damage during the dressing change process, which greatly hinders wound healing and causes pain and inflammation in patients. Therefore, hydrogel dressings are required to have good mechanical properties and adjustable adhesion properties, so that the hydrogel can quickly adapt to wound changes and avoid damage to the wound. At the same time, while achieving effective adhesion to the wound, the hydrogel dressing should also take into account the adjustable adhesion of the dressing to facilitate replacement and reduce damage to the wound tissue. Summary of the invention

[0004] In order to overcome the problems that existing hydrogel dressings have a single function and cannot meet the complex and diversified clinical needs in the healing process of infected wounds, the present invention provides an on-demand debonding multifunctional hydrogel and a preparation method and application thereof.

[0005] The present invention is achieved through the following technical solutions:

[0006] A multifunctional hydrogel with on-demand debonding, the raw materials of which include 1-vinylimidazole, acrylic acid, acrylic acid-N-succinimidyl ester and MoS2@TA / Fe NTs; the preparation steps include:

[0007] S1. Dispersing MoS2@TA / Fe NTs in deionized water to form a MoS2@TA / Fe NTs dispersion;

[0008] S2. Add 1-vinylimidazole, acrylic acid and acrylic acid-N-succinimidyl ester to the MoS2@TA / Fe NTs dispersion and stir to form a homogeneous solution;

[0009] S3. Adding an initiator and a cross-linking agent to the solution to react, thereby obtaining a multifunctional hydrogel that can be debonded on demand.

[0010] Furthermore, the preparation steps of the MoS2@TA / Fe NTs include: first dissolving sulfur powder and ammonium molybdate in an anhydrous ethanol solution containing octylamine to react to obtain MoS2 NTs, and then adding TA solution and FeCl3 solution to the dispersion containing MoS2 NTs to react to obtain MoS2@TA / Fe NTs.

[0011] Furthermore, the mass fraction of MoS2@TA / Fe NTs in the MoS2@TA / Fe NTs dispersion is 0.03-0.12wt%.

[0012] Furthermore, the mass ratio concentration of acrylic acid in the homogeneous solution is 34-36%; the mass ratio concentration of 1-vinylimidazole in the homogeneous solution is 3.4-5.6%; and the mass ratio concentration of acrylic acid-N-succinimidyl ester in the homogeneous solution is 0.4%.

[0013] Furthermore, the mass ratio concentration of acrylic acid in the homogeneous solution is 36%; the mass ratio concentration of 1-vinylimidazole in the homogeneous solution is 3.9%; and the mass ratio concentration of acrylic acid-N-succinimidyl ester in the homogeneous solution is 0.4%.

[0014] Furthermore, the initiator is ammonium persulfate, and the cross-linking agent is N,N′-methylenebisacrylamide.

[0015] Furthermore, the mass ratio concentration of the added initiator is 0.4%, and the added amount of the cross-linking agent is 0.01%.

[0016] Furthermore, the reaction temperature is 55-60°C and the reaction time is 5-10 min.

[0017] Furthermore, the reaction temperature is 60°C and the reaction time is 10 min.

[0018] Furthermore, the hydrogel is applied to wound dressing.

[0019] Compared with the prior art, the beneficial effects are:

[0020] The method of the present invention mainly uses polyacrylic acid as a matrix, forms a copolymer network with 1-vinylimidazole and acrylic acid-N-succinimidyl ester, and uses it as a hydrogel matrix to load MoS2@TA / Fe NTs. The carboxyl group of acrylic acid and the imidazole group of 1-vinylimidazole can form hydrogen bonds to enhance the stability and tensile strength of the hydrogel. MoS2@TA / Fe NTs and the imidazole group and carboxyl group inside the hydrogel realize their loading in the hydrogel network through non-covalent interactions such as hydrogen bonds, and have catalytic activity similar to natural enzymes. As a powerful antioxidant, it can neutralize and remove free radicals in the body, and help prevent cell damage and aging caused by oxidative stress.

[0021] The hydrogel of the present invention can be used for tight adhesion to dynamic wounds. The carboxylic acid group of acrylic acid can destroy the hydration isolation layer on the surface of wet tissues, and form hydrogen bonds with amino groups on the skin. The imidazole of 1-vinylimidazole produces electrostatic interactions with negatively charged groups on the skin, and the NHS group of acrylic acid-N-succinimidyl ester forms a stable amide bond with the primary amino group of skin tissue. The three synergistically achieve stable wet wound adhesion. The nitrogen atom of the imidazole group of 1-vinylimidazole forms a complex structure with zinc ions through coordination bonds. The good responsiveness of the imidazole group of 1-vinylimidazole to zinc ions can realize the function of debonding the hydrogel on demand. In addition, 1-vinylimidazole can affect the permeability and anabolism of bacterial cell membranes, change the permeability of cell membranes, and combine with the photothermal response of MoS2@TA / Fe NTs to give the hydrogel excellent antibacterial activity, promote the proliferation of new blood vessels and hair follicles at the wound site, accelerate collagen deposition, and effectively promote the healing of infected wounds. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a schematic diagram of the preparation process and formation mechanism of hydrogel;

[0023] Figure 2 is the SEM image of the prepared MoS2@TA / Fe NTs;

[0024] Figure 3 is the SEM image of the prepared hydrogel;

[0025] Figure 4 is the tensile stress-strain diagram of the hydrogel;

[0026] Figure 5 is the adhesion strength diagram of hydrogels with different components;

[0027] Figure 6 This is a diagram of the on-demand debonding effect of the hydrogel;

[0028] Figure 7 is the antibacterial performance diagram of the hydrogel;

[0029] Figure 8 is the antioxidant performance diagram of the hydrogel;

[0030] Fig. 9 This is a diagram of the healing analysis of infected wounds using hydrogels. DETAILED DESCRIPTION

[0031] The following is further explained and illustrated in conjunction with the examples, but the specific examples do not limit the present invention in any form. If not specifically stated, the methods and equipment used in the examples are conventional methods and equipment in the art, and the raw materials used are all conventional commercially available raw materials.

[0032] Example 1

[0033] This embodiment provides a method for preparing MoS2@TA / Fe NTs, and the preparation steps include:

[0034] S1. Mix 1.2mmol sulfur powder and 0.075mmol ammonium molybdate [(NH4)6Mo7O 24 4H2O] was dissolved in a mixture consisting of 13 mL of anhydrous ethanol and 14 mL of octylamine. The resulting solution was stirred thoroughly until completely homogeneous and then transferred to a Teflon-lined container.

[0035] S2. The container was sealed and placed in an autoclave, which was sealed and heated in an air oven at 200°C for 24 hours. After completion, the autoclave was brought to room temperature by cooling, and the synthesized product was collected by centrifugation. Finally, the collected product was washed several times with anhydrous ethanol and vacuum dried overnight to obtain MoS2 NTs.

[0036] S3. Disperse 100 mg MoS2 uniformly in deionized water, add 3 mL TA solution (40 mg / mL), and continue stirring for 20 minutes. Add 2 mL of 10.6 mg / mL FeCl3·6H2O solution, continue stirring for 10 minutes, and adjust the pH value of the solution to 7.5 with 1 M NaOH. Then, centrifuge at 8000 rpm for 5 minutes to collect the precipitated black precipitate, wash it several times with ultrapure water and anhydrous ethanol, and vacuum dry it for 24 hours to obtain MoS2@TA / Fe NTs.

[0037] Example 2

[0038] This embodiment provides a multifunctional hydrogel that can be debonded on demand, and the preparation steps include:

[0039] S1. Disperse 0.03 g of MoS2@TA / Fe NTs into 6 ml of deionized water and disperse them by ultrasonic for ten minutes to prepare a MoS2@TA / Fe NTs dispersion;

[0040] S2. Add 3.66 g of acrylic acid, 0.34 g of 1-vinyl imidazole and 0.04 g of acrylic acid-N-succinimide ester to the MoS2@TA / Fe NTs dispersion in step S1, dissolve, stir evenly to obtain a mixed solution, and react to form a homogeneous solution;

[0041] S3. Add 0.04 g of thermal initiator and 0.001 g of cross-linking agent to the homogeneous solution and inject it into the mold. Place it in a 60°C environment to react for 10 minutes to obtain a multifunctional hydrogel that can be debonded on demand.

[0042] Example 3

[0043] This embodiment provides a multifunctional hydrogel that can be debonded on demand, and the preparation steps include:

[0044] S1. Disperse 0.03 g of MoS2@TA / Fe NTs into 6 ml of deionized water and disperse them by ultrasonic for ten minutes to prepare a MoS2@TA / Fe NTs dispersion;

[0045] S2. Add 3.61 g of acrylic acid, 0.39 g of 1-vinyl imidazole and 0.04 g of acrylic acid-N-succinimide ester to the MoS2@TA / Fe NTs dispersion in step S1, dissolve, stir evenly to obtain a mixed solution, and react to form a homogeneous solution;

[0046] S3. Add 0.04 g of thermal initiator and 0.001 g of cross-linking agent to the homogeneous solution and inject it into the mold. Place it in a 60°C environment to react for 10 minutes to obtain a multifunctional hydrogel that can be debonded on demand.

[0047] Example 4

[0048] This embodiment provides a multifunctional hydrogel that can be debonded on demand, and the preparation steps include:

[0049] S1. Disperse 0.03 g of MoS2@TA / Fe NTs into 6 ml of deionized water and disperse them by ultrasonic for ten minutes to prepare a MoS2@TA / Fe NTs dispersion;

[0050] S2. Add 3.54 g of acrylic acid, 0.46 g of 1-vinyl imidazole and 0.04 g of acrylic acid-N-succinimide ester to the MoS2@TA / Fe NTs dispersion in step S1, dissolve, stir evenly to obtain a mixed solution, and react to form a homogeneous solution;

[0051] S3. Add 0.04 g of thermal initiator and 0.001 g of cross-linking agent to the homogeneous solution and inject it into the mold. Place it in a 60°C environment to react for 10 minutes to obtain a multifunctional hydrogel that can be debonded on demand.

[0052] Example 5

[0053] This embodiment provides a multifunctional hydrogel that can be debonded on demand, and the preparation steps include:

[0054] S1. Disperse 0.03 g of MoS2@TA / Fe NTs into 6 ml of deionized water and disperse them by ultrasonic for ten minutes to prepare a MoS2@TA / Fe NTs dispersion;

[0055] S2. Add 3.44 g of acrylic acid, 0.56 g of 1-vinyl imidazole and 0.04 g of acrylic acid-N-succinimide ester to the MoS2@TA / Fe NTs dispersion in step S1, dissolve, stir evenly to obtain a mixed solution, and react to form a homogeneous solution;

[0056] S3. Add 0.04 g of thermal initiator and 0.001 g of cross-linking agent to the homogeneous solution and inject it into the mold. Place it in a 60°C environment to react for 10 minutes to obtain a multifunctional hydrogel that can be debonded on demand.

[0057] Example 6

[0058] This embodiment provides a multifunctional hydrogel that can be debonded on demand, and the preparation steps include:

[0059] S1. Disperse 0.03 g of MoS2@TA / Fe NTs into 6 ml of deionized water and disperse them by ultrasonic for ten minutes to prepare a MoS2@TA / Fe NTs dispersion;

[0060] S2. Add 3.61 g of acrylic acid, 0.39 g of 1-vinyl imidazole and 0.04 g of acrylic acid-N-succinimide ester to the MoS2@TA / Fe NTs dispersion in step S1, dissolve, stir evenly to obtain a mixed solution, and react to form a homogeneous solution;

[0061] S3. Add 0.04 g of thermal initiator and 0.001 g of cross-linking agent to the homogeneous solution and inject it into the mold. Place it in a 60°C environment to react for 10 minutes to obtain a multifunctional hydrogel that can be debonded on demand.

[0062] Example 7

[0063] This embodiment provides a multifunctional hydrogel that can be debonded on demand, and the preparation steps include:

[0064] S1. Disperse 0.06 g of MoS2@TA / Fe NTs into 6 ml of deionized water and disperse them by ultrasonic for ten minutes to prepare a MoS2@TA / Fe NTs dispersion;

[0065] S2. Add 3.61 g of acrylic acid, 0.39 g of 1-vinyl imidazole and 0.04 g of acrylic acid-N-succinimide ester to the MoS2@TA / Fe NTs dispersion in step S1, dissolve, stir evenly to obtain a mixed solution, and react to form a homogeneous solution;

[0066] S3. Add 0.04 g of thermal initiator and 0.001 g of cross-linking agent to the homogeneous solution and inject it into the mold. Place it in a 60°C environment to react for 10 minutes to obtain a multifunctional hydrogel that can be debonded on demand.

[0067] Example 8

[0068] This embodiment provides a multifunctional hydrogel that can be debonded on demand, and the preparation steps include:

[0069] S1. Disperse 0.09 g of MoS2@TA / Fe NTs into 6 ml of deionized water and disperse them by ultrasonic for ten minutes to prepare a MoS2@TA / Fe NTs dispersion;

[0070] S2. Add 3.61 g of acrylic acid, 0.39 g of 1-vinyl imidazole and 0.04 g of acrylic acid-N-succinimide ester to the MoS2@TA / Fe NTs dispersion in step S1, dissolve, stir evenly to obtain a mixed solution, and react to form a homogeneous solution;

[0071] S3. Add 0.04 g of thermal initiator and 0.001 g of cross-linking agent to the homogeneous solution and inject it into the mold. Place it in a 60°C environment to react for 10 minutes to obtain a multifunctional hydrogel that can be debonded on demand.

[0072] Example 9

[0073] This embodiment provides a multifunctional hydrogel that can be debonded on demand, and the preparation steps include:

[0074] S1. Disperse 0.12 g of MoS2@TA / Fe NTs into 6 ml of deionized water and disperse them by ultrasonic for ten minutes to prepare a MoS2@TA / Fe NTs dispersion;

[0075] S2. Add 3.61 g of acrylic acid, 0.39 g of 1-vinyl imidazole and 0.04 g of acrylic acid-N-succinimide ester to the MoS2@TA / Fe NTs dispersion in step S1, dissolve, stir evenly to obtain a mixed solution, and react to form a homogeneous solution;

[0076] S3. Add 0.04 g of thermal initiator and 0.001 g of cross-linking agent to the homogeneous solution and inject into the mold, place in a 60°C environment to react for 10 minutes to obtain an on-demand debonding multifunctional hydrogel wound dressing.

[0077] Comparative Example 1

[0078] S1. Disperse 0.03 g of MoS2@TA / Fe NTs into 6 ml of deionized water and disperse them by ultrasonic for ten minutes to prepare a MoS2@TA / Fe NTs dispersion;

[0079] S2. Add 3.44 g of acrylic acid to the MoS2@TA / Fe NTs dispersion in step S1 and dissolve it, stir it evenly to obtain a mixed solution, and react to form a homogeneous solution;

[0080] S3. Add 0.04 g of thermal initiator and 0.001 g of cross-linking agent to the homogeneous solution and inject it into the mold. Place it in a 60°C environment to react for 10 minutes to obtain a multifunctional hydrogel that can be debonded on demand.

[0081] Comparative Example 2

[0082] S1. Disperse 0.03 g of MoS2@TA / Fe NTs into 6 ml of deionized water and disperse them by ultrasonic for ten minutes to prepare a MoS2@TA / Fe NTs dispersion;

[0083] S2. Add 3.44 g of acrylic acid and 0.56 g of 1-vinyl imidazole to the MoS2@TA / Fe NTs dispersion in step S1, dissolve them, stir them evenly to obtain a mixed solution, and react to form a homogeneous solution;

[0084] S3. Add 0.04 g of thermal initiator and 0.001 g of cross-linking agent to the homogeneous solution and inject it into the mold. Place it in a 60°C environment to react for 10 minutes to obtain a multifunctional hydrogel that can be debonded on demand.

[0085] Performance Testing

[0086] 1. Electron microscope detection

[0087] Depend on Figure 2 It can be seen that the MoS2@TA / Fe NTs prepared in the present invention is a hollow tubular structure. The hollow structure of the MoS2 nanotube provides a larger specific surface area and has more active sites, which is helpful for the loading of the TA / Fe complex. At the same time, since tannic acid and iron ions are complexed and coated on the surface of the molybdenum disulfide nanotubes, the surface morphology is relatively rough.

[0088] Depend on Figure 3 It can be seen that the microscopic morphology of the on-demand debonding multifunctional hydrogel wound dressing prepared by the present invention presents a three-dimensional porous structure with uniform pore size, and MoS2@TA / Fe NTs can be evenly dispersed in the hydrogel.

[0089] 2. Mechanical properties testing

[0090] The on-demand debonding multifunctional hydrogel wound dressing prepared in the example was subjected to mechanical property testing. The hydrogel was subjected to a tensile test at a rate of 100 mm / min on a universal testing machine equipped with a 1000N load cell. The experimental results are shown in Table 1 below:

[0091] Table 1

[0092]

[0093] From Table 1 and Figure 4 It can be seen that the tensile strength of the hydrogel prepared by the present invention can reach 217.88 KPa, the tensile strain at break is 1346%, the elastic modulus is 0.088 MPa, and the tear energy is as high as 1.42 MJ / m 2 ,The hydrogel has good ductility and elasticity, and can meet the requirements of wound dressings in dynamic human skin locations.

[0094] 3. Adhesion performance test

[0095] Figure 5 The load-displacement curves and adhesion properties of Comparative Example 1, Comparative Example 2 and Example 5 on pig skin. Figure 5 It can be seen that the adhesion strength of the pure polyacrylic acid hydrogel without 1-vinylimidazole and acrylic acid-N-succinimidyl ester in Comparative Example 1 is 28.61 KPa, and the adhesion energy is 43.54 J / m 2 The hydrogel with 1-vinylimidazole added in Comparative Example 2 showed higher adhesion strength (32.85 KPa) and adhesion energy (60.91 J / m 2 ), which is attributed to the electrostatic interaction between the imidazole of 1-vinyl imidazole and the negatively charged groups on the skin, which improves the adhesion performance of the hydrogel. The hydrogel in Example 5 has stronger adhesion strength (37.46 KPa) and adhesion energy (60.95 J / m 2 ), this is because the NHS group of acrylate-N-succinimidyl ester forms a stable amide bond with the primary amino group of skin tissue, further improving the adhesion strength of the hydrogel.

[0096] The on-demand debonding multifunctional hydrogel wound dressing prepared in Example 5 was tested for adhesion performance. A 20 mm × 20 mm × 2 mm (length × width × thickness) hydrogel sample test pattern was used, fixed on a universal mechanical testing machine, in contact with different materials, and the shear rate was set to 5 mm / min. The obtained adhesion performance is shown in Table 2:

[0097] Table 2

[0098] Adhesion strength(KPa) <![CDATA[Adhesion energy (J / m 2 ) <!-- 6 -->]]> Glass 29.10 11.88 iron plate 33.35 14.35 Aluminum Plate 39.21 20.34 Pigskin 37.46 60.95

[0099] The adhesive interface between the hydrogel of the on-demand debonding multifunctional hydrogel wound dressing prepared in Example 5 and the pig skin was immersed in water with different concentrations of Zn 2+ The immersion time in the solution was 20 s, and the adhesion strength before and after immersion was analyzed by lap shear test, as shown in Table 3.

[0100] Table 3

[0101] <![CDATA[Zn 2+ Concentration (mol / L)]]> Adhesion strength(KPa) 0 43.20 0.05 37.91 0.1 30.75 0.15 25.78 0.2 22.32

[0102] In order to study the effect of treatment time on the debonding effect, the bonding interface was placed in Zn 2+ The samples were immersed in the solution (concentration of 0.05 mol / L) for different time periods (0s, 20s, 40s, 60s) to evaluate their adhesion strength, as shown in Table 4.

[0103] Table 4

[0104] Immersion time(s) Adhesion strength(KPa) 0 43.03 20 38.16 40 22.16 60 9.21

[0105] From Table 2, Table 3, Table 4 and Figure 6 It can be seen that the on-demand debonding multifunctional hydrogel wound dressing prepared by the method of the present invention can achieve an adhesion strength of 58.02KPa on the skin, and can provide excellent adhesion effect. The MTH adhered to pig skin was soaked in zinc ion solutions of different concentrations for 20s. In a 0.2mol / L zinc ion solution, its adhesion strength dropped from the initial 43.2KPa to 22.3KPa. The MTH adhered to pig skin was soaked in a 0.05mol / L zinc salt solution for different times (0s, 20s, 40s, 60s), and the corresponding viscosity strengths were 43KPa, 38.1KPa, 22.1KPa and 9.2KPa, respectively. The presence of zinc ions significantly reduced the adhesion performance of MTH, which is attributed to the fact that zinc ions not only partially destroyed the electrostatic interaction between the hydrogel and the wet tissue, but also shielded the electrostatic interaction in the hydrogel network, thereby negatively affecting the interface of the gel. It can be seen that the present invention has good debonding performance and is effective for Zn 2+ The solution has a high response sensitivity, achieving close fit and controllable adhesion to infected wounds, and can perform "painless and non-destructive" dressing changes within 1 minute.

[0106] 4. Antibacterial performance testing

[0107] The antibacterial properties of the on-demand debonding multifunctional hydrogel wound dressing prepared in Example 5 against Staphylococcus aureus and Escherichia coli under near-infrared light irradiation were determined by a flat plate coating method.

[0108] Depend on Figure 7It can be seen that when there is no NIR irradiation, the survival rate of bacteria in the hydrogel group with 1-vinylimidazole is lower than that of the hydrogel without 1-vinylimidazole, showing a higher antibacterial effect, with the survival rate of E.coli being 86.51% and the survival rate of S.aureus being 89.12%. When there is no NIR irradiation, the survival rate of E.coli in the hydrogel group containing both 1-vinylimidazole and MoS2@TA / Fe NTs is 60.05%, and the survival rate of S.aureus is 30.39%. When the hydrogel group containing both 1-vinylimidazole and MoS2@TA / Fe NTs is irradiated with NIR for 600s, the survival rate of E.coli is 0.79%, and the survival rate of S.aureus is 3.19%. The gradual improvement of the antibacterial effect is attributed to the fact that the imidazole groups in the hydrogel can directly interact with the microbial cell membrane, resulting in increased membrane permeability, and MoS2@TA / Fe NTs perform photothermal antibacterial. The two methods work together to give the hydrogel excellent antibacterial properties under NIR.

[0109] 5. Antioxidant performance test

[0110] The antioxidant capacity of the on-demand debonding multifunctional hydrogel wound dressings prepared in Examples 5 to 8 was tested by using the organic free radical scavenging DPPH method. The decrease in the absorption of A525 after adding different MoS2@TA / Fe NTs component contents was measured by spectrophotometry using the absorption peak of the characteristic purple-red group of the DPPH solution to indicate its ability to eliminate organic free radicals. The obtained antioxidant properties are shown in Table 5:

[0111] Table 5

[0112] DPPH clearance rate (%) Example 5 52.2 Example 6 69.9 Example 7 82.6 Example 8 93.7

[0113] From Table 5 and Figure 8 It can be seen that the on-demand debonding multifunctional hydrogel wound dressing prepared by the method of the present invention has an excellent scavenging ability for DPPH, indicating that the hydrogel has good antioxidant properties.

[0114] 6. Infection Wound Healing Experiment

[0115] The on-demand debonding multifunctional hydrogel wound dressing prepared in Example 5 was used for the experiment. A full-thickness skin wound infection model of mice infected with MRSA was established. The mice were divided into three groups, including a control group, a hydrogel, and a NIR+hydrogel. Near-infrared laser (808nm, 0.8W cm-2) was applied for 600 seconds on days 0, 1, 3, and 5. During the experiment, the wounds were measured and photographed to record the wound repair process. The hydrogel samples were replaced when the wounds were photographed. The wound closure rate at each time point was calculated as follows: Wound closure rate (%) = An day / A0 day × 100%, where A0 day and An day represent the wound area treatment on day 0 and day n, respectively (n = 3, 7, and 14). The close fit and wound repair effects of the hydrogel samples were studied. The accelerated wound healing performance of the hydrogel was evaluated by the wound closure rate. After 14 days of treatment, H&E staining, Masson staining, and CD31 staining were performed to evaluate the wound healing mechanism. Through comprehensive evaluation, a basic evaluation of the wound healing effect of the hydrogel dressing was made. The obtained infected wound healing effect data are shown in Table 6:

[0116] Table 6

[0117]

[0118]

[0119] From Table 6 and Fig. 9 It can be seen that the on-demand debonding multifunctional hydrogel wound dressing prepared by the present invention can promote the healing and tissue repair of infected wounds, promote collagen deposition and angiogenesis, and is expected to become a candidate biomaterial in the field of clinical infected wound treatment.

[0120] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A multifunctional hydrogel with on-demand debonding, characterized in that: The raw materials include 1-vinylimidazole, acrylic acid, acrylic acid-N-succinimidyl ester and MoS2@TA / Fe NTs; The preparation steps include: S1. Dispersing MoS2@TA / Fe NTs in deionized water to form a MoS2@TA / Fe NTs dispersion; S2. Add 1-vinylimidazole, acrylic acid and acrylic acid-N-succinimidyl ester to the MoS2@TA / Fe NTs dispersion and stir to form a homogeneous solution; S3. Adding an initiator and a cross-linking agent to the solution to react, thereby obtaining a multifunctional hydrogel that can be debonded on demand.

2. The on-demand debonding multifunctional hydrogel according to claim 1, characterized in that: The preparation steps of the MoS2@TA / Fe NTs include: firstly dissolving sulfur powder and ammonium molybdate in an anhydrous ethanol solution containing octylamine to react and prepare MoS2NTs, then adding TA solution and FeCl3 solution to the dispersion containing MoS2NTs to react and prepare MoS2@TA / Fe NTs.

3. The on-demand debonding multifunctional hydrogel according to claim 1, characterized in that: The mass fraction of MoS2@TA / Fe NTs in the MoS2@TA / Fe NTs dispersion is 0.03-0.12 wt %.

4. The on-demand debonding multifunctional hydrogel according to claim 1, characterized in that: The mass ratio concentration of acrylic acid in the homogeneous solution is 34-36%; the mass ratio concentration of 1-vinyl imidazole in the homogeneous solution is 3.4-5.6%; the mass ratio concentration of acrylic acid-N-succinimide ester in the homogeneous solution is 0.4%.

5. The on-demand debonding multifunctional hydrogel according to claim 4, characterized in that: The mass ratio concentration of acrylic acid in the homogeneous solution is 36%; the mass ratio concentration of 1-vinyl imidazole in the homogeneous solution is 3.9%; and the mass ratio concentration of acrylic acid-N-succinimide ester in the homogeneous solution is 0.4%.

6. The on-demand debonding multifunctional hydrogel according to claim 1, characterized in that: The initiator is ammonium persulfate, and the cross-linking agent is N,N'-methylenebisacrylamide.

7. The on-demand debonding multifunctional hydrogel according to claim 1, characterized in that: The mass ratio concentration of the added initiator is 0.4%, and the added amount of the cross-linking agent is 0.01%.

8. The on-demand debonding multifunctional hydrogel according to claim 1, characterized in that: The reaction temperature is 55-60°C and the reaction time is 5-10 minutes.

9. The on-demand debonding multifunctional hydrogel according to claim 8, characterized in that: The reaction temperature is 60°C and the reaction time is 10 min.

10. The on-demand debonding multifunctional hydrogel according to any one of claims 1 to 9, characterized in that: The hydrogel is applied to wound dressing.